Once a week consumption of Western diet over twelve weeks promotes sustained insulin resistance and non-alcoholic fat liver disease in C57BL/6 J mice - Thainá Magalhães Demaria; Leticia Diniz Crepaldi; Emylle Costa-Bartuli; Jessica Ristow Branco; Patricia Zancan; Mauro Sola-Penna (Scientific Reports, 2023)
Abstract The Western diet (high in fat and sucrose) consumption is a highly prevalent feature in the whole world, mainly due to the increasing consumption of ultra-processed foods (UPF), which are cheaper and easier-to-eat, as compared to fresh and highly nutritive meals. Epidemiological studies have associated UPF consumption with development of obesity, non-alcoholic fat liver disease (NAFLD) and insulin resistance. For molecular studies, mice fed with Western diets have been used to characterize signaling pathways involved in these diet-induced pathologies. However, these studies fed mice continuously with the diets, which is not compatible with what occurs in real life, when consumption is occasional. Here, we fed mice once-a-week with a high fat, high sucrose (HFHS) diet and compared these animals with those fed continuously with HFHS diet or with a standard diet. Our results show that after a single day of consuming HFHS, animals presented impaired oral glucose tolerance test (oGTT) as compared to control group. Although this impairment was reversed after 24 h consuming regular diet, repetition of HFHS consumption once-a-week aggravated the picture such as after 12-weeks, oGTT impairment was not reversed after 6 days under control diet. Liver steatosis, inflammation, impaired insulin signaling pathway and endoplasmic reticulum stress are similar comparing animals that consumed HFHS once-a-week with those that continuously consumed HFHS, though weekly-fed animals did not gain as much weight. Therefore, we conclude that regimen of one day HFHS plus 6 days normal diet over 12 weeks is sufficient to induce insulin resistance and NAFLD in mice.